Current treatment of Carrion's disease - Zegarra Araujo, Napoleón (1957)
Carrion's disease, therapeutic raises three issues, which are: 1. The high mortality. 2. Impossibility until at will produce this syndrome in animals. and 3. The recovery without treatment, which occurs in many cases.